Clinical spectrum of intra-abdominal abscesses in children admitted to the pediatric emergency department - Chun-Yu Chen; Mao-Jen Lin; Wen-Chieh Yang; Yu-Jun Chang; Feng-Xia Gao; Han-Ping Wu (Journal of Microbiology, Immunology and Infection, 2020)
Background: To analyze clinical spectrum of intra-abdominal abscesses in children and find helpful clinical parameters could aid physicians in earlier detection and differential diagnosis. Methods: From 2004 to 2011, we retrospectively analyzed 66 pediatric patients, aged 18 years or younger with intra-abdominal abscesses. The data were obtained and studied: demographics, clinical presentations, etiologies, laboratory tests, microbiology, imaging studies, treatment modalities, complications and long-term outcomes. Results: There were 66 patients (mean age, 9.27 ± 4.16 years) diagnosed as intra-abdominal abscesses. The two most common presented symptoms were fever and abdominal pain (90.9%; 78.8%, respectively). Most patients presented with leukocytosis (81.8%) and elevated C-reactive protein (CRP) levels (95.5%). In patients with abscesses in solid organs, urine white blood cell counts, nitrate and leukocyte esterase were all significant parameters (all P < 0.05), and urine pH and specific gravity were both lower than those in non-solid organs (P = 0.026; P = 0.043, respectively). Escherichia coli (E. coli) was the most common organism cultured from renal abscess. Streptococcus viridans was the most common organism cultured from liver abscess. Moreover, the two most predominant bacteria in periappendical and intraperitoneal abscesses were E. coli and Bacteroides fragilis. Conclusions: We suggest that primary physicians should keep this disease in mind when children present with predisposing risk factors, fever, abdominal pain, leukocytosis and elevated CRP level. Besides, we recommend the urinary analysis or ultrasonography (US) is valuable in patients with fever and abdominal pain. Keywords: Intra-abdominal abscesses, Children, Emergency department